2009
DOI: 10.1089/cap.2008.0144
|View full text |Cite
|
Sign up to set email alerts
|

A 6-Week, Randomized, Double-Blind, Placebo-Controlled Study of the Efficacy and Safety of Risperidone in Adolescents with Schizophrenia

Abstract: Risperidone 1-3 mg/day and 4-6 mg/day were well tolerated and effective in adolescents experiencing acute episodes of schizophrenia. The benefit-risk profile suggests that a dose of 1-3 mg/day might be optimal for this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(81 citation statements)
references
References 28 publications
5
74
0
2
Order By: Relevance
“…Our subjects were 1-2 years younger than the 3.5-4 years age typical of puberty onset and an accompanying growth spurt in male macaque monkeys. Other findings of no excessive weight gain in many young children treated with risperidone (Fraguas et al 2008;Haas et al 2009) suggest that our result is not too surprising. Also, our adequate but not excessive monkey chow diet, supplemented with fruits and vegetables, does not lend itself to overeating or excessive caloric intake.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…Our subjects were 1-2 years younger than the 3.5-4 years age typical of puberty onset and an accompanying growth spurt in male macaque monkeys. Other findings of no excessive weight gain in many young children treated with risperidone (Fraguas et al 2008;Haas et al 2009) suggest that our result is not too surprising. Also, our adequate but not excessive monkey chow diet, supplemented with fruits and vegetables, does not lend itself to overeating or excessive caloric intake.…”
Section: Discussionsupporting
confidence: 49%
“…Placebo was given to all animals during weeks 1-2 of the postdrug phase, and then all treats were discontinued. These dose levels are in the low-to-moderate dose equivalence by body weight for children (e.g., Fraguas et al 2008;Haas et al 2009). …”
Section: Group Assignment and Dosingmentioning
confidence: 99%
See 1 more Smart Citation
“…Other adverse effects, such as weight gain, may be similar in patients treated with the lower doses (0.5 to 2.5 mg) typically used to treat disruptive and aggressive behaviour, compared with higher doses (3 to 6 mg). 50,51 For children and adolescents with behavioural problems associated with ADHD who have inadequate response or intolerable adverse effects with ADHD medications and risperidone, little evidence is available to guide subsequent pharmacotherapy. Similarly, aside from data on risperidone, little evidence is available to guide pharmacotherapy for children and adolescents with disruptive or aggressive Canadian Guidelines on Pharmacotherapy for Disruptive and Aggressive Behaviour in Children and Adolescents With ADHD, ODD, or CD behaviour in the absence of ADHD.…”
mentioning
confidence: 99%
“…Some studies did not assess ECG modifications [36][37][38][39][40][41], and so a meta-analytic approach was not possible [12•]. In short-term studies, no effect on ECG was reported in 13 studies with risperidone [32,[42][43][44][45][46][47][48][49][50][51][52][53]. One study reported prolonged QT interval in one patient with risperidone [54].…”
Section: Lengthening Of the Qt Intervalmentioning
confidence: 99%